KINERJA APARAT KANTOR WALI NAGARI DAN PENGARUHNYA TERHADAP KEPUASAN MAYARAKAT DALAM PELAYANAN PUBLIK - Hazana, Deby; Adnan, M. Fachri (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2022)
This study seeks to test hypotheses by utilizing samples taken from the community. This research was conducted in Nagari Taluak located in Lintau Buo District. In this study, the sampling method used was the accidental sampling method. A total of 98 participants in this study were sampled. At the Nagari Taluak Guardian's Office located in Lintau Buo District, the results showed that the performance variable had a positive or significant effect on the public service satisfaction variable. This is by taking into account the significance value of 0.000 < 0.05 for the performance variable on the public service satisfaction scale. At the Nagari Taluak Guardian's Office located in Lintau Buo District, the magnitude of the influence of the performance variable on the public service satisfaction variable was 0.243 or equivalent to 24.3 percent. This amount of 24.3 percent is calculated using the Adjusted R Square value.